2001
DOI: 10.1023/a:1011093612868
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The low number of distinct dislocation slip systems (two) is characteristic of a brittle material and is consistent with the observation that paracetamol will tolerate only deformations of 1 part in 10(6) before fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 6 publications
3
31
0
1
Order By: Relevance
“…In Section 4, we show the results of our simulations of plastic deformation of paracetamol and sucrose single crystals. Our simulations reproduce a yield stress y $ 200 MPa for paracetamol and y $ 1 GPa for sucrose, in good agreement with experimental observation [23][24][25].…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…In Section 4, we show the results of our simulations of plastic deformation of paracetamol and sucrose single crystals. Our simulations reproduce a yield stress y $ 200 MPa for paracetamol and y $ 1 GPa for sucrose, in good agreement with experimental observation [23][24][25].…”
Section: Introductionsupporting
confidence: 87%
“…We simulated stress-strain curves for different values of slip plane distances. Our simulations show that a slip plane distance d ¼ 2b 1 ¼ 1:88 nm gives a yield stress y ¼ 150-250 MPa, which is a good estimate of the value of the yield stress observed in experiments, y $ 200 MPa [24]. Therefore, we assume that the slip plane distance is d ¼ 9.4 nm.…”
Section: Paracetamol Single Crystalsmentioning
confidence: 52%
See 2 more Smart Citations
“…However, in the case of the butyl paraben, longer and more bulky alkyl chains provide resistance to the gliding of the slip planes; therefore, higher hardness compared to the ethyl and propyl parabens were observed. Duncan-Hewitt et al [101] and Finnie et al [102] performed indentation studies on paracetamol (acetaminophen) and revealed that the hardness varied as a function of indenter orientation with the crystallographic direction within the indentation planes. …”
Section: Indentation-induced Plasticity In Parabens and Paracetamolmentioning
confidence: 99%